Liaison Psychiatry During the Peak of the Coronavirus Pandemic: A Description of Referrals and Interventions - López-Atanes, Mayte; González-Briceño, Juan Pablo; Abeal-Adham, Adrián; Fuertes-Soriano, Sara; Cabezas-Garduño, Janire; Peña-Rotella, Álvar; Sáenz-Herrero, Margarita (Frontiers in Psychiatry, 2021)
Introduction: The novel coronavirus SARS-CoV-2 belongs to the coronavirus, a group of viruses that can cause upper respiratory infections in humans. It can course as an asymptomatic infection or as a more severe disease requiring hospitalization. Neuropsychiatric symptoms have been described in the acute phase of the illness and as long-term repercussions. We describe the patient characteristics and interventions. Materials and Methods: This is an observational descriptive prospective study. This study was carried out within the Department of Psychiatry of Cruces University Hospital. Data from each psychiatric consultation within our consultation-liaison service were obtained from Mar 17 to Apr 17, 2020. We recruited clinical and referral characteristics and psychiatric interventions. Results: Of a total of 721 SARS-CoV-2 hospitalizations, 43 (5,6%) patients were referred to our psychiatry liaison service. The median age was 61 years old, and 62,8% were women. The infectious disease Department was the most frequent petitioner (37,2%), and the most common reason for referral was patient anxiety (25,6%). A total of 67,4% of patients received psychological counseling and 55,8% some pharmacological approach, with a median of 3,7 visits/calls per patient. In addition, 20,3% needed a medication switch due to potential interactions between psychotropics and drugs used to treat SARS-CoV-2. Discussion: In our study, up to 5,6% of SARS-CoV-2 hospitalized patients needed a psychiatric evaluation, especially for anxiety and mood symptoms. Psychosocial factors associated with the pandemic, drugs used to treat the infection, or a direct causative effect of the virus may explain our findings.